Bridging the gap: ICU nurses experiences in detecting pressure injuries across diverse skin tones - Hollywood, Eleanor; Derwin, Rosemarie (My University, 2025)
Background: Pressure Injury detection remains a challenge in patients with darker skin tones due to the absence of visible erythema, resulting in delayed diagnosis and poorer patient outcomes. Despite international guidelines, nurses face barriers in early recognition due to knowledge gaps and inadequate training in skin tone diversity. A timely assessment is critical for effective treatment. This necessitates that healthcare professionals recognise how early pressure ulcer signs may present in patients of all skin tone types. Aim: To explore ICU nurses’ experiences in assessing pressure areas in patients with dark skin tones and identify challenges and solutions. Methodology: Following ethical approval, semi-structured interviews were conducted with 11 ICU Nurses. Interview data were analysed using thematic analysis using NVivo software. Findings: Three key themes emerged: (1) Gaps in education and training on diverse skin tones, (2) Challenges in early detection due to “white normativity” in assessment tools, and (3) The need for inclusive education and advanced diagnostic tools to mitigate disparities. Conclusion: Urgent improvements in nursing curricula and clinical training are required to ensure equitable pressure injury detection for all skin tones. The study advocates for greater inclusivity in educational materials, continuous professional development, and the integration of advanced tools like infrared thermography and subepidermal moisture scanners.
PUBLISHED
Keywords: Pressure injury; Nurse education; Skin tone; Unconscious bias; Diversity; White normativity; Intensive care; Inclusive Society; Acute care nursing; Nursing Education; Other; Health